Faktor Dan Peranan Menonton Tayangan Televisi Animasi Pada Kemampuan Bahasa Anak Usia Kelompok B Di Paud Terpadu Golden Fun Kids Masaran Sragen Tahun Ajaran 2016/2017 - Juwita Sari, Cony Ayuk; , Sri Slamet, M.Pd, M.Hum (2017)
Cony Ayuk Juwita Sari / A52013006. Factors and The Effect Of Watching Animation Television on Children's Language Abilities AgeGroup B In Early Childhood Golden Fun Kids Integrated Masaran Sragen The Academic Year Of 2016/2017. Research paper. Teacher Training and Education faculty.Universitas Muhammadiyah Surakarta. March, 2017. The research on grup B in early childhood Golden Fun Kids Integrated Masaran Sragen was motivated by many animated a the children liked them different languages. Animation was the process of creating motion effects that occurred some time the results looked the real. The research of the purpose were determine factors and the effect of watching animation on the language ability of children's age group B in early childhood Golden Fun Kids Integrated Masaran Sragen The academic year of 2016/2017. The method used was descriptive qualitative research. Data collection techniques using interviews, quetionnaires, and documentation. The results of the research were internal factors and eksternal factors. Internal factors was from chidren them self and eksternal factors was from the friend and the parents. There was a positive the effect to help effect children's language ability, introduction of number, colors and knowledge. While negative the effect was that children were lazy to do the activities. They also imitated the bad language. To prevent negative animation film impact of parents doing mentoring. In conclusion the internal factors are more dominant.There are positive and negative effect to children when they are watching the animation. Keywords: Factor and The Effect of watching television, Animation, Language Ability